Analysis of the TRIGA MARK-II benchmark IEU-COMP-THERM-003 with Monte Carlo code OpenMC (Journal of Bangladesh Academy of Sciences, 2024)
Ensuring the reliable use of particle transport computer codes necessitates verification against benchmark experiments. This study aims to verify the Monte Carlo code OpenMC using the criticality benchmark model IEUCOMP- THERM-003 from the International Criticality Safety Benchmark Evaluation Project (ICSBEP) Handbook. The analysis focuses on the TRIGA Mark II reactor cores 132 and 133, employing nuclear cross-section libraries ENDF/B-VIII.0, ENDF/B-VII.1, ENDF/B-VII.0, and ENDF/BVI. 2. Results show that OpenMC provides KEFF values in close agreement with benchmark values, demonstrating its robustness in neutronic simulations. Comparison with MVP code results obtained previously, particularly with JENDL-3.3, shows similar accuracy.J. Bangladesh Acad. Sci. 48(2); 231-236: December 2024